Appearance learning for 3D tracking of robotic surgical tools. (February 2014) - Reiter, Austin; Allen, Peter K; Zhao, Tao
In this paper, we present an appearance learning approach which is used to detect and track surgical robotic tools in laparoscopic sequences. By training a robust visual feature descriptor on low-level landmark features, we build a framework for fusing robot kinematics and 3D visual observations to track surgical tools over long periods of time across various types of environment. We demonstrate 3D tracking on multiple types of tool (with different overall appearances) as well as multiple tools simultaneously. We present experimental results using the da Vinci ® surgical robot using a combination of both ex-vivo and in-vivo environments.